Character Education and Implementation in Learning at MAN 1 Banjarmasin - Tamjidnor Tamjidnor (LAFADZ JAYA Publisher, 2022)
The purpose of this study was to find out how MAN 1 Banjarmasin implements character education in learning, and to determine the factors that influence character education in MAN 1 Banjarmasin learning. This research is descriptive and qualitative research. The object of this research amounted to 6 people, including the head of the madrasa, waka of the course, several teachers, and several students. Using data collection techniques from interviews, observation, and recording. The results of the research of MAN 1 Banjarmasin on the implementation of character education in learning include learning planning and learning implementation. At the lesson plan stage, the teacher includes various characters in the lesson plan to be applied in learning. At the implementation stage of learning, the teacher internalizes character values in the initial, core, and final activities aimed at developing student character. There is a kind of stimulus or interactive stimulus in the learning process, its function is to instill personality in the learning process. In the implementation stage of learning, teachers also use various methods to shape students' character, namely exploring children's knowledge and skills through lectures, discussions, demonstrations, and questions and answers, and they use scientific methods to make the learning process more focused on student activities. student character formation. Only then can the implementation of character education in language learning be carried out properly. There are two factors that influence the implementation of character education learning at MAN 1 Banjarmasin, namely supporting factors and inhibiting factors. Supporting factors include activities carried out in religious schools to support the successful formation of student character and school environmental conditions. Inhibiting factors include the time of learning implementation, students or students from different backgrounds, and lesson plans.